The Effect of Leadership, Competency and Talents Management to Career Development Through Employees Performance of BPJS Health of Regional Division II - Fadillah, Erwin; Hendriani, Susi; Samsir, Samsir (International Journal of Economic, Business & Applications, 2018)
This study was aimed to determine and analyze the influence between Leadership, Competence, and Talent Management on Career Development BPJS Health Division II Regional Performance as a variable Mediation. The population of this study were all leaders in BPJS Health Division II with the level of manager and assistant manager who totaled 121 people. The sample in this research is 99 people obtained by disproportionate stratified random sampling method. The instrument used for data collection is by ordinal scale model questionnaire. To test the hypothesis used descriptive analysis and PLS analysis.The result of data analysis shows that (1) the leadership has a significant positive effect on career development, (2) the competence has a significant positive effect on career development, (3) the competence has a significant negative effect on career development, (4) talent management has no significant positive effect on the development (5) leadership has a negative effect on insignificant to career development, (6) competence has no significant positive effect on leadership performance, (7) talent management has significant negative effect on leadership performance, (8) leadership performance is not a mediation variable between leadership career development, (9) leadership performance is not a mediating variable between competence on career development, (10) and leadership performance is not a mediating variable between talent management towards career development.